A novel Silicon on Insulator MOSFET with an embedded heat pass path and source side channel doping. (February 2016) - Karbalaei, Mohammad; Dideban, Daryoosh
Abstract: In this paper we introduce a novel Silicon on Insulator Metal Oxide Semiconductor Field Effect Transistor (SOI MOSFET) with an embedded silicon heat pass path in the buried oxide (HPP-SOI). As this silicon path in the buried oxide conducts the generated heat in the active silicon channel from the shortest and most efficient path, self-heating effect improves while the fabrication process of this structure will remain without complexity. Moreover, the introduction of dopants in the source side of the channel leads to improvement in the leakage current, subthreshold slope, DIBL and threshold voltage roll-off in comparison with conventional SOI MOSFET (C-SOI). As proposed HPP-SOI structure shows these positive features, this structure can be considered as a serious candidate in nanoscale high temperature integrated applications. Highlights: We have introduced an efficient and short path to avoid self heating effect. Addition of P-dopants to channel in the source side improves Short Channel Effects (SCE). We have evaluated HPP-SOI figures of merit in comparison with conventional SOI structures. The width of Silicon heat pass path in the buried oxide layer is optimized in terms of its impact on the device parameters.